The necessity for measurement of left atrial pressure after cardiac valve surgery - Sarin, C. L. (1970)
Left and right atrial pressures were monitored in 100 patients undergoing open heart surgery for acquired valvular disease of the heart at St. Thomas' Hospital. The right atrial pressure bore no constant relationship to the left atrial pressure in 61% of the patients and there was no reliable way of deducing left atrial pressure from the right. We believe that it is imperative to measure both right and left atrial pressures if post-operative management after cardiac valve surgery is to be effective. There has been no instance of pulmonary oedema or postperfusion syndrome in our practice since its introduction.